2019
DOI: 10.1073/pnas.1816424116
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale modeling reveals formation of an epigenetically driven HOXC gene hub

Abstract: Gene expression is orchestrated at the structural level by nucleosome positioning, histone tail acetylation, and linker histone (LH) binding. Here, we integrate available data on nucleosome positioning, nucleosome-free regions (NFRs), acetylation islands, and LH binding sites to "fold" in silico the 55-kb HOXC gene cluster and investigate the role of each feature on the gene's folding. The gene cluster spontaneously forms a dynamic connection hub, characterized by hierarchical loops which accommodate multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 66 publications
(63 reference statements)
2
69
0
Order By: Relevance
“…The heterogeneity has now been confirmed by direct imaging of individual chromosomal structures [14][15][16]. As a consequence of this conformational plasticity, statistical ensembles [25,26,29,30,[33][34][35][36][37][38] must be used in order to describe chromosomal structures in vivo.…”
Section: A Polymer Model Of Chromatin Based On Epigenetics Features Cmentioning
confidence: 99%
“…The heterogeneity has now been confirmed by direct imaging of individual chromosomal structures [14][15][16]. As a consequence of this conformational plasticity, statistical ensembles [25,26,29,30,[33][34][35][36][37][38] must be used in order to describe chromosomal structures in vivo.…”
Section: A Polymer Model Of Chromatin Based On Epigenetics Features Cmentioning
confidence: 99%
“…All these features of directed folding were combined into our recent folding of the HOXC gene cluster to reveal a functionally important contact hub …”
Section: Illustrative Studies: Mesoscale Modeling To Help Interpret Ementioning
confidence: 99%
“…Our group developed a mesoscale chromatin model where initially nucleosomes were flat cylinders with core electrostatics described by a set of Debye‐Hückel charges that reproduce the electric field around the atomistic nucleosome using the Poisson‐Boltzmann potential; linker DNA was treated using Stigter's worm‐like chain model . Further improvements in our chromatin model included the explicit description of histone tails as coarse‐grained beads, various LHs, epigenetic marks, implicit account of magnesium ions, and variable nucleosome positions . Validation against experimental data has shown that mesoscale models capture the essential physical properties of chromatin fibers, and thus contribute to our understanding of the different levels of DNA organization inside the cell and their relevance to regulation of gene expression .…”
Section: Introduction: Technology Innovations As Triggers Of Field Admentioning
confidence: 99%
“…Several attempts have been made to understand the 3D organization of the genome using a variety of techniques developed previously to understand the statics and dynamics of polymers (15)(16)(17)(18)(19)(20)(21)(22). Early models revealed both the fractal nature of individual chromosome folding and the larger scale packing of all the chromosomes into TADs of various sizes (23,24).…”
Section: Introductionmentioning
confidence: 99%